Anthropogenic pressures reshaping the ecosystem of Burullus lagoon (Nile Delta): Diatom evidence of post-Aswan Dam perspective - Yanna Wang; Zhongpeng Yang; Huawei Wang; Ting Zhu; Said A. Shetaia; Alaa Salem; Xinxin Li; Maotian Li; Jing Chen; Zhongyuan Chen (Marine Pollution Bulletin, 2026)

Nutrition and feeds for abalone: Current knowledge and future directions - Xinxin Li; Dong Huang; Mingzhu Pan; Javad Sahandi; Zhenhua Wu; Kangsen Mai; Wenbing Zhang (Reviews in Aquaculture, 2024)
Abalone is a commercially important mariculture mollusc because of its nutrient‐rich value and extensive market demand. To date, over 95% of the abalone supply has been contributed by farming. Macroalgae are the natural food of abalones. However, the supply of macroalgae is unstable owing to seasonal restrictions. This limits the success of abalone farming. Therefore, formulated diets are crucial for the ongoing expansion and sustainable development of abalone culture. The most important considerations in formulated diets are the nutrient composition and commercially available feed ingredients. This review presents a comprehensive description of the nutrient requirements of abalones and the role that nutrients play in regulating abalone growth and health. The dietary proteins, lipids, carbohydrates, macroalgae sources and feed additives currently used in abalone feeds were subsequently summarised. Additionally, this review also highlights the importance of prioritizing the development of sustainable alternative sources of proteins, carbohydrates and macroalgae to meet the increasing demand for abalone feed. Based on the information provided, future directions in the knowledge of abalone nutrition and feeds are subsequently discussed, which will guide further research towards the development of well‐balanced commercial feeds that enhance feed utilisation and promote abalone growth and health.